Formation of andesite melts and Ca‐rich plagioclase in the submarine Monowai volcanic system, Kermadec arc. (13th December 2015) - Kemner, Fabian; Haase, Karsten M.; Beier, Christoph; Krumm, Stefan; Brandl, Philipp A.
Abstract: Andesites are typical rocks of island arcs and may either form by fractional crystallization processes or by mixing between a mafic and a felsic magma. Here we present new petrographic and geochemical data from lavas of the submarine Monowai volcanic system in the northern Kermadec island arc that display a continuous range in composition from basalt to andesite. Using petrology, major, trace, and volatile element data, we show that basaltic magmas mostly evolve to andesitic magmas by fractional crystallization. Our thermobarometric calculations indicate that the formation of the large caldera is related to eruption of basaltic‐andesitic to andesitic magmas from a magma reservoir in the deeper crust. Small variations in trace element ratios between the caldera and the large active cone imply a homogeneous mantle source. Contrastingly, resurgent dome melts of the caldera stagnated at shallower depths are more depleted and show a stronger subduction input than the other edifices. The Monowai basaltic glasses contain less than 1 wt % H2 O and follow typical tholeiitic fractionation trends. High‐An plagioclase crystals observed in the Monowai lavas likely reflect mixing of H2 O‐saturated melt batches with hot and dry tholeiitic, decompression melt batches. The result is a relatively H2 O‐poor mafic magma at Monowai implying that partial melting of the mantle wedge is only partly due to the volatile flux and that adiabatic melting may play a significant role in the formation of the parental melts of the Monowai volcanic system and possibly other arc volcanoes. Key Points: The Monowai volcanic system shows complete range from basalts to andesites Formation of the andesites can be best explained by fractional crystallization Petrographic evidence for mixing of adiabatic dry and hydrous fluid‐fluxed melt batches